Xenobiotic Nucleic Acid (XNA) Synthesis by Phi29 DNA Polymerase. Issue 2 (18th May 2018) - Torres, Leticia L.; Pinheiro, Vitor B.
Abstract: Phi29 DNA polymerase (DNAP) is the replicative enzyme of the Bacillus subtilis bacteriophage Phi29. Its extraordinary processivity and its ability to perform isothermal amplification of DNA are central to many molecular biology applications, including high‐sensitivity detection and large‐scale production of DNA. We present here Phi29 DNAP as an efficient catalyst for the production of various artificial nucleic acids (XNAs) carrying backbone modifications such as 1, 5‐anhydrohexitol nucleic acid (HNA), 2′‐deoxy‐2′‐fluoro‐arabinonucleic acid (FANA), and 2′‐fluoro‐2′‐deoxyribonucleic acid (2′‐fluoro‐DNA). A full protocol for the synthesis of HNA polymers by an exonuclease‐deficient variant (D12A) of Phi29 DNAP plus a detailed guide for the design and test of novel XNA synthetase reactions performed by Phi29 DNAP are provided. © 2018 by John Wiley & Sons, Inc.